Hurler Syndrome - Rao, Kalipatnam Seshagiri; Adhikari, Sudhir; Singh, Sandeep; Poudel, Shankar; Basnet, Sahisnuta; Bishwakarma, Ganesh (Journal of Nepal Paediatric Society, 2017)
We report a case of Hurler syndrome in 10 years old boy diagnosed on the basis of classical clinical and radiological features. Early diagnosis, genetic counseling and regular follow up with recent modalities of treatment can decrease mortality significantly and the child may grow normally. J Nepal Paediatr Soc 2016;36(3):295-297